Strategi Membangun Resiliensi Narapidana Tindak Pidana Narkotika Di Lapas Narkotika KELAS IIA Jakarta - Sipahutar, Daniel Lukman; Muhammad, Ali (Innovative: Journal Of Social Science Research, 2024)
The issue of drug abuse in Indonesia presents a significant challenge for correctional institutions, particularly the Narcotics Correctional Facility Class IIA Jakarta. The high prevalence of drug users in Indonesia adds complexity to the rehabilitation efforts for inmates involved in these offenses. This article aims to analyze the strategies used in building resilience among narcotics crime inmates at the Narcotics Correctional Facility Class IIA Jakarta. Resilience is viewed as a crucial capability that inmates must develop to withstand the pressures of the prison environment and prepare themselves for reintegration into society after their incarceration period. Through a literature review and analysis of rehabilitation programs implemented in the correctional facility, this article finds that programs combining psychological support, skill training, and spiritual activities have significant potential in building inmate resilience. However, challenges remain in the implementation of these programs, including ongoing evaluation and enhanced social support. Therefore, this article recommends further development of existing programs to ensure their effectiveness in building inmate resilience and preparing them for reintegration into society.